Islamic Finance as a Catalyst for Economic Growth: Insights from Indonesia - Zahirah, Putri; Marlinda, Marlinda; Muliadi, Muliadi; Hadi, Rizal (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2025)
Islamic finance has emerged as a viable alternative to conventional financial systems, playing an increasingly important role in promoting financial inclusion both in Indonesia and globally. This study investigates the dynamic relationship between macroeconomic variables, Islamic finance, and economic growth in Indonesia, considering both short- and long-term perspectives. Employing the Vector Error Correction Model (VECM), the research utilizes monthly time series data spanning from January 2011 to December 2023. The model includes gross fixed capital formation, trade openness, and inflation as macroeconomic indicators; Islamic bank financing, Sharia mutual funds, and sukuk as proxies for Islamic finance; and GDP at constant prices as a proxy for economic growth. The findings indicate that, in the short run, inflation has a significantly negative effect on economic growth. In contrast, in the long run, all selected Islamic finance indicators—as well as gross fixed capital formation and trade openness—exhibit a significant positive relationship with economic growth. Granger causality tests reveal unidirectional causality from economic growth to both capital formation and Sharia mutual funds, and from trade openness to inflation. Additional unidirectional relationships are observed from inflation to both economic growth and sukuk issuance; from capital formation to sukuk and mutual funds; and from Islamic bank financing to both inflation and sukuk. These results highlight the critical role of Islamic financial development in supporting economic growth and contributing to poverty alleviation. This study offers a valuable contribution as one of the first empirical investigations into the macroeconomic significance of Islamic finance in Indonesia.======================================================================================================== ABSTRAK - Keuangan Syariah sebagai Katalisator Pertumbuhan Ekonomi: Bukti dari Indonesia. Keuangan syariah telah muncul sebagai solusi kredibel terhadap sistem keuangan konvensional, dengan peran yang semakin signifikan dalam mendorong inklusi keuangan, baik di Indonesia maupun global. Kajian ini mengeksplorasi dinamika hubungan antara variabel makroekonomi, keuangan syariah, dan pertumbuhan ekonomi di Indonesia, baik dalam jangka pendek maupun jangka panjang. Analisis didasarkan pada data time series bulanan periode Januari 2011 sampai Desember 2023, menggunakan metode VECM, dengan indikator makroekonomi seperti pembentukan modal tetap bruto, keterbukaan perdagangan, dan inflasi; indikator keuangan syariah berupa pembiayaan bank syariah, reksa dana syariah, dan sukuk; serta PDB atas harga konstan sebagai proksi pertumbuhan ekonomi. Hasil penelitian menunjukkan bahwa dalam jangka pendek, inflasi berdampak negatif signifikan terhadap pertumbuhan ekonomi. Sebaliknya, dalam jangka panjang, seluruh indikator keuangan syariah yang diuji, bersama dengan pembentukan modal tetap bruto dan keterbukaan perdagangan, menunjukkan hubungan positif yang signifikan terhadap pertumbuhan ekonomi. Uji Kausalitas Granger menunjukkan bahwa hubungan kausalitas hanya terjadi dalam satu arah, yaitu dari pertumbuhan ekonomi ke pembentukan modal tetap bruto dan reksadana syariah, keterbukaan perdagangan ke inflasi, inflasi ke pertumbuhan ekonomi dan sukuk, pembentukan modal tetap bruto ke sukuk dan reksada syariah, pembiayaan bank syariah ke inflasi dan sukuk. Hasil penelitian ini menunjukkan bahwa pertumbuhan lembaga keuangan syariah akan memberikan kontribusi positif terhadap pertumbuhan ekonomi yang menjadi elemen krusial dalam mengurangi kemiskinan. Studi ini berkontribusi sebagai salah satu kajian empiris awal mengenai peran makroekonomi keuangan syariah di Indonesia.